Systematics, biogeography and echolocation of tube-nosed bats genus murina (Chiroptera: vespertilionidae) in mainland Southeast Asia - Pipat Soisook (Prince of Songkla University, 2014)
Thesis (Ph.D.,Biology)--Prince of Songkla University, 2013